background image

3.1 Existence of no more than one monovalued injective reloid for a given
pair of filter objects

3.1.1 The lemmas

The lemmas in this section were provided to me by Robert Martin Solovay in [5]. These are based
on Wistar Comfort’s work.

In this section we will assume

µ

is an ultrafilter on a set

I

and

f

:

I

I

has the property

X

µ

f

1

X

µ

.

Lemma 64.

If

X

µ

then

X

∩ h

f

i

X

µ

.

Proof.

If

h

f

i

X

µ

then

X

f

1

h

f

i

X

µ

and so

X

µ

. Thus

X

µ

∧ h

f

i

X

µ

and

consequently

X

∩ h

f

i

X

µ

.

We will say that

x

is

periodic

when

f

n

(

x

) =

x

for some positive integer

x

. The least such

n

is

called

the period

of

x

.

Let’s define

x

y

iff there exist

i, j

N

such that

f

i

(

x

) =

f

j

(

y

)

. Trivially it is an equivalence

relation. If

x

and

y

are periodic, then

x

y

iff exists

n

N

such that

f

n

(

y

) =

x

.

Let

A

=

{

x

I

|

x

is periodic with period

>

1

}

.

We will show that

A

µ

. Let’s assume

A

µ

.

Let a set

D

A

contains (by the axiom of choice) exactly one element from each equivalence

class of

A

defined by the relation

.

Let

α

is a function

A

N

defined as follows. Let

x

A

. Let

y

be the unique element of

D

such

that

x

y

. Let

α

(

x

)

be the least

n

N

such that

f

n

(

y

) =

x

.

Let

B

0

=

{

x

A

|

α

(

x

)

is even

}

and

B

1

=

{

x

A

|

α

(

x

)

is odd

}

.

Let

B

2

=

{

x

A

|

α

(

x

) = 0

}

.

[TODO: Two below lemmas have very similar proofs. Can we refactor it?]

Lemma 65.

B

0

∩ h

f

i

B

0

B

2

.

Proof.

If

x

B

0

∩ h

f

i

B

0

then

f

n

(

y

) =

x

for a minimal even

n

and

x

=

f

(

x

)

where

f

m

(

y

) =

x

for a minimal even

m

. Thus

f

n

(

y

) =

f

(

x

)

thus

y

and

x

laying in the same equivalence class and

thus

y

=

y

. So we have

f

n

(

y

) =

f

m

+1

(

y

)

. Thus

n

6

m

+ 1

by minimality.

x

lies on an orbit and thus

x

=

f

1

(

x

)

where by

f

1

I mean step backward on our orbit;

f

m

(

y

) =

f

1

(

x

)

and thus

x

=

f

n

1

(

y

)

thus

n

1

>

m

by minimality or

n

= 0

.

Thus

n

=

m

+ 1

what is impossible for even

n

and

m

. We have a contradiction what proves

B

0

∩ h

f

i

B

0

⊆ ∅

.

Remained the case

n

= 0

, then

x

=

f

0

(

y

)

and thud

α

(

x

) = 0

.

Lemma 66.

B

1

∩ h

f

i

B

1

=

.

Proof.

Let

x

B

1

∩ h

f

i

B

1

. Then

f

n

(

y

) =

x

for an odd

n

and

x

=

f

(

x

)

where

f

m

(

y

) =

x

for an

odd

m

. Thus

f

n

(

y

) =

f

(

x

)

thus

y

and

x

laying in the same equivalence class and thus

y

=

y

. So

we have

f

n

(

y

) =

f

m

+1

(

y

)

. Thus

n

6

m

+ 1

by minimality.

x

lies on an orbit and thus

x

=

f

1

(

x

)

where by

f

1

I mean step backward on our orbit;

f

m

(

y

) =

f

1

(

x

)

and thus

x

=

f

n

1

(

y

)

thus

n

1

>

m

by minimality (

n

= 0

is impossible because

n

is odd.

Thus

n

=

m

+ 1

what is impossible for odd

n

and

m

. We have a contradiction what proves

B

0

∩ h

f

i

B

0

=

.

Lemma 67.

B

2

∩ h

f

i

B

2

=

.

Proof.

Let

x

B

2

∩ h

f

i

B

2

. Then

x

=

y

and

x

=

y

where

x

=

f

(

x

)

. Thus

x

=

f

(

x

)

and so

x

A

what is impossible.

Lemma 68.

A

µ

.

Proof.

Suppose

A

µ

.

Ordering of filters

11